2011
DOI: 10.1016/j.jmr.2011.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution DNP NMR with solvent mixtures: Substrate concentration and radical extraction

Abstract: Dynamic nuclear polarization (DNP) followed by sudden sample dissolution, is a topic of active investigation owing to the method's unique prospects for the delivery of NMR spectra and images with unprecedented sensitivity. This experiment achieves hyperpolarization by the combined effects of electron-nuclear irradiation and cryogenic operation; the exploitation of these states occurs following a sudden melting and flushing of the resulting pellet from its original environment into a conventional, liquid-state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 16 publications
2
45
0
1
Order By: Relevance
“…Approaches to minimize the dilution of HP analytes include use of immiscible liquids for the melting and flushing of the DNP sample; this significantly reduces the amount of aqueous solvent required. 79 …”
Section: Considerations For Dnp Probe Developmentmentioning
confidence: 99%
“…Approaches to minimize the dilution of HP analytes include use of immiscible liquids for the melting and flushing of the DNP sample; this significantly reduces the amount of aqueous solvent required. 79 …”
Section: Considerations For Dnp Probe Developmentmentioning
confidence: 99%
“…The same issue also arises during the infusion of hyperpolarized molecules into the blood stream, during the time lag before reaching the targeted organs for in vivo applications, as well as during the signal acquisition. Multiple strategies have been explored and developed in the last years for minimizing losses of polarization, such as the use of fast fluid transfer devices [19], the rapid elimination of the free radicals [20][21][22], or the storage of hyperpolarization in the form of long-lived states (LLS) [23][24][25][26][27][28].…”
mentioning
confidence: 99%
“…Relaxation losses are exacerbated by remaining paramagnetic PAs that no longer serve any function after dissolution; thus, one of the most effective ways to slow down the relaxation rate R 1 ( 13 C) and hence, prolong the lifetime of the polarization P( 13 C) is to eliminate the radicals (14). For some radicals, such as trityls, separation can be achieved by solvent extraction (15) or precipitation by a jump in pH followed by mechanical filtration through a stack of polyethylene filters (16,17). Lumata et al (18,19) have shown that precipitation can be used for 1,3 bisdiphenylene-2-phenylallyl (BDPA) and 2,2 diphenyl-1-picrylhydrazyl (DPPH).…”
mentioning
confidence: 99%